PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, STRES KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN AKADEMI MANAJEMEN DMINISTRASI YOGYAKARTA - Hartadi, Agung (LPPM Akademi Manajemen Administrasi Yogyakarta, 2021)
This research is motivated by the importance of the importance of the leadership's attention at AMA Yogyakarta to their employees in order to be able to improve their performance. This study aims to determine the effect of work environment, work discipline, work stress and compensation on employee performance at the Yogyakarta Administrative Management Academy. This research with 27 respondents. The results show work environment, work discipline, work stress and compensation a positive and significant effect on employee performance. The coefficient of determination (R2) shows a value of 0.818.